1996
DOI: 10.3109/00365519609090579
|View full text |Cite
|
Sign up to set email alerts
|

Export of guanosine 3′,5′-cyclic monophosphate (cGMP) from human erythrocytes characterized by inside-out membrane vesicles

Abstract: The present study was undertaken to characterize the export of cGMP from human erythrocytes at 37 degrees C. Inside-out membrane vesicles were exposed to cGMP and [3H]-cGMP in the presence and absence of 2 mmol l-1 ATP. In the absence of ATP, an equilibrium was reached within 15 min for the lowest tested concentration (0.65 mumol l-1), and the amount of cGMP in the vesicles was linearly correlated to the cGMP concentrations in the incubate. These observations suggest that the ATP-independent process represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
29
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 21 publications
8
29
0
Order By: Relevance
“…The knowledge about the structure and function of the protein families involved in cGMP synthesis and degradation has grown vastly the last years, whereas little was known so far about the molecular identity of the proteins that mediate the cellular export. Studies in membrane vesicles from human erythrocytes suggested that cGMP is transported by an organic anion transport ATPase (12)(13)(14). The reported characteristics of this transport system in erythrocytes, including the K m value of 2.4 M for cGMP (13) and the lack of affinity for the MRP1 substrate leukotriene C 4 (14), are similar to our findings on MRP5-mediated cGMP transport (see Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The knowledge about the structure and function of the protein families involved in cGMP synthesis and degradation has grown vastly the last years, whereas little was known so far about the molecular identity of the proteins that mediate the cellular export. Studies in membrane vesicles from human erythrocytes suggested that cGMP is transported by an organic anion transport ATPase (12)(13)(14). The reported characteristics of this transport system in erythrocytes, including the K m value of 2.4 M for cGMP (13) and the lack of affinity for the MRP1 substrate leukotriene C 4 (14), are similar to our findings on MRP5-mediated cGMP transport (see Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Both cAMP, as well as cGMP, secretion has been shown to be unidirectional and energy-dependent (4 -8, 10). Furthermore, a primary active transport of cGMP has been demonstrated directly in inside-out membrane vesicles from human erythrocytes (12)(13)(14). The transport of both cyclic nucleotides has been shown to be inhibited by probenecid, suggesting that this export is mediated by a transporter for amphiphilic anions (10,13,15).…”
mentioning
confidence: 97%
“…Erythrocyte membranes express at least two transporters for glutathione conjugates [2,4,45], one with a high affinity for DNP-SG (K d ~2 μM) and identifiable as MRP1 and another with a low affinity (K d > ~60 μM) [4]. There are also cGMP transporters, one with a low affinity (K d 50 -80 μM) [4] and another with a high affinity (K d ~ 1 μM) [46]. This latter probably contributes less, perhaps much less, than 20% of the transport even at the lowest concentrations [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although an initial report suggested that MRP4 is a high-affinity cGMP transporter [24], this was not confirmed by later work (see Table 1). An accumulating body of indirect evidence [103] suggests that MRP4 is the main transporter responsible for the efflux of messenger cGMP from erythrocytes [24,48,85,89,93,104]. However, all experiments were conducted in vitro with inside-out membrane vesicles prepared from either cultured cell lines or erythrocytes.…”
Section: Cyclic Nucleotide Transport By Mrp4mentioning
confidence: 99%
“…cGMP efflux from intact erythrocytes has not yet been demonstrated and there is no evidence that mature erythrocytes can actually make cGMP. The physiological relevance of cGMP efflux by MRP4 from erythrocytes is, therefore, questionable, especially as MRP4 transports cGMP with low affinity [48,85,101]. In view of the observed high rate of cGMP transport by erythrocyte vesicles, MRP4 might limit the ability of erythrocytes to accumulate base/nucleoside analogs.…”
Section: Cyclic Nucleotide Transport By Mrp4mentioning
confidence: 99%